Metode Komunikasi Panti Asuhan Darul Aitam Medan dalam Membina Akhlak Anak Asuh - Wahyu Candra; Rubino Rubino (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The Darul Aitam Orphanage provides social services and care for neglected children. Researchers say that abandoned children's behavior is basically very well controlled. As a result, the goal of this study was to learn how Darul Aitam Medan orphanage staff members communicate with one another to instill moral values in their children. Case study research and qualitative methods are used in this field study. The data for the research were gathered through observations and interviews. Using hiwar strategies, tabligh strategies, tadzkir techniques, tabsyir strategies, indzar techniques, and appeal techniques, this study reveals how parental figures at the Darul Aitam Medan shelter use specific strategies in building ethics. Youngsters who generally supplicate multiple times in gathering, regard and welcome guardians, guardians and visitors, and assist with cleaning the shelter with other encourage kids show that this method of correspondence decidedly affects them. It is anticipated that the Orphanage will become one of the educational development institutions that helps students, particularly orphans or children who cannot afford it, develop their personalities.